Alice's piano the life of Alice Herz-Sommer - Müller, Melissa 1967-; Piechocki, Reinhard 1949- (St. Martin's Press, 2012)
Chronicles the life of the oldest living Holocaust survivor, a classically trained pianist who used her love of music to provide hope to her fellow sufferers at the Theresienstadt concentration camp.